The room of white fire : a novel - Parker, T. Jefferson (G.P. Putnam's Sons, 2017)
"From three-time Edgar Award winner and New York Times bestseller T. Jefferson Parker, a stirring new thriller about a private investigator tasked with hunting down a returned soldier broken and made dangerous by his experiences at war"--